Alkaline battery capable of improving low-temperature discharge performance and preparation method thereof
By using metal-doped composite manganese dioxide, zinc alloy paste, modified electrolyte and dopamine-coated separators in alkaline batteries, the problem of degradation of battery performance in low-temperature environments is solved, and excellent discharge performance under extremely low temperature conditions is achieved.
Patent Information
- Application Number
- CN202510078728.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-17
- Publication Date
- 2025-04-25
AI Technical Summary
The ion migration capacity of alkaline batteries is reduced due to the freezing of electrolyte in low temperature environments, affecting the battery capacity and output power.
Metal-doped composite manganese dioxide is used as the positive electrode material, and the conductivity and low-temperature electrochemical activity are improved through Ni2+, Co2+, Fe3+ metal ion doping and polypyrrole coating; the negative electrode zinc paste reduces freezing point through alloying treatment of nano-zinc powder and anti-low-temperature additives to improve reaction efficiency; ethylene glycol and nano-zirconium dioxide are added to the electrolyte to improve ion migration ability; the separator is pre-impregnated by dopamine coating and potassium hydroxide solution to enhance the wetting and ion migration efficiency of the electrolyte.
It effectively improves the discharge capacity, output power and service life of alkaline batteries in low temperature environments, so that they also have excellent discharge performance under extremely low temperature conditions.
Smart Images

Figure BDA0005247865810000141 
Figure BDA0005247865810000142 
Figure BDA0005247865810000151
Abstract
Description
Technical Field
[0001] The invention relates to the field of alkaline batteries, and in particular to an alkaline battery with improved low-temperature discharge performance and a preparation method thereof. Background Art
[0002] Alkaline batteries are an electrochemical energy storage device with potassium hydroxide solution as the electrolyte. Due to their high energy density, good cycle performance and long storage life, they have been widely used in portable electronic devices, lighting equipment and emergency power supply.
[0003] However, when alkaline batteries are used in low temperature environments, especially when the temperature is below minus 20°C, the temperature of the electrolyte is lower than its freezing point, resulting in ice formation. The formation of ice crystals not only reduces the concentration of mobile ions in the electrolyte, but also increases the resistance to ion migration, thereby reducing the rate of chemical reactions, affecting the capacity and output power of the battery, and significantly reducing the performance of alkaline batteries, severely limiting their application under low temperature conditions. Therefore, how to overcome the ice formation problem of alkaline batteries in low temperature environments, improve the low temperature performance of the electrolyte and maintain the activity of the electrochemical reaction has become a technical problem that needs to be solved urgently.
[0004] Therefore, the prior art has defects and needs to be improved. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide an alkaline battery having improved ion migration capability, enhanced reaction efficiency under low temperature conditions and improved low temperature discharge performance and a preparation method thereof.
[0006] To achieve this object, the present invention adopts the following technical solutions:
[0007] A method for preparing an alkaline battery with improved low-temperature discharge performance comprises the following steps:
[0008] S1. Preparation of a positive electrode ring of a battery: The positive electrode material of the battery contains the following components in parts by weight: 90-110 parts of metal-doped composite manganese dioxide, 1-2 parts of a binder, and 8-12 parts of a 30-40wt% potassium hydroxide solution. The positive electrode material and water are stirred and mixed in a mass ratio of 10-15:1 to form a positive electrode powder, and then the positive electrode ring is obtained by pressing, molding, and screening;
[0009] S2. Prepare a negative electrode zinc paste for a battery: mix nano zinc powder, indium powder and gallium powder in a mass ratio of 92:4:4, mechanically ball-mill the mixed powder under argon protection to obtain alloyed zinc powder, then ultrasonically mix the alloyed zinc powder with a composite conductive additive accounting for 2-4wt% by mass, then add a composite binder accounting for 10-15wt% by mass to the mixture, stir evenly to form a slurry, add an anti-low temperature additive accounting for 5-7wt% by mass to the slurry, and treat it in a high-speed shear disperser for 30-60 minutes to obtain a negative electrode zinc paste;
[0010] The anti-low temperature additive is a deep eutectic solution, propylene glycol and 1-ethyl-3-methylimidazolium tetrafluoroborate in a mass ratio of 6-8:2-3:0.5-1, and the deep eutectic solution is a transparent liquid formed by stirring and mixing choline chloride and ethylene glycol in a molar ratio of 1:2;
[0011] S3, inserting the positive electrode ring obtained in step S1 into the battery steel shell, inserting a diaphragm into the positive electrode ring, and then injecting electrolyte into the diaphragm, eliminating bubbles by vacuuming, and standing for 30-40 minutes until the electrolyte completely infiltrates the diaphragm;
[0012] S4, injecting the negative electrode zinc paste obtained in step S2 into the battery steel shell, inserting the negative electrode current collector, and obtaining an alkaline battery with improved low-temperature discharge performance after sealing and packaging.
[0013] Using the above technical solution, the preparation process of metal-doped composite manganese dioxide is as follows: manganese dioxide powder, carbon nanotubes and graphene are mixed in a mass ratio of 96:2:2, and ethanol accounting for 20-40wt% by mass is added to promote dispersion;
[0014] It is then placed in an ultrasonic disperser for 30-60 minutes, and then a polypyrrole precursor solution with a mass percentage of 1-2wt% is added, and an in-situ polymerization reaction is carried out at 50-60°C for 1-2 hours to obtain a composite manganese dioxide coated with a conductive polymer, which is then doped with metal ions to obtain a metal-doped composite manganese dioxide.
[0015] The specific process of metal ion doping treatment using the above technical solution is: placing the composite manganese dioxide coated with the conductive polymer in a mixed metal salt solution with a concentration of 0.1-0.2 mol / L at a mass volume ratio of 1:50, and performing a solvent thermal reaction at 105-120°C for 4-6 hours to form a composite manganese dioxide preliminarily doped with metal ions; wherein the mixed metal salt solution contains Ni 2+, Co2+ and Fe3+ metal ions, and the molar ratio of the metal examples is 1:1:1. Subsequently, the composite manganese dioxide preliminarily doped with metal ions is filtered and washed, and placed in a 0.5 mol / L nickel nitrate hexahydrate solution at a mass volume ratio of 1:30, and immersed for 6-12 hours under stirring conditions to enhance the doping depth, and then dried at 65-80°C, and calcined at a temperature of 525-550°C for 2-3 hours under argon protection to obtain the metal-doped composite manganese dioxide.
[0016] Using the above technical scheme, the preparation process of the mixed metal salt solution is: dissolving nickel nitrate hexahydrate, cobalt nitrate hexahydrate and iron nitrate nonahydrate in deionized water in a molar ratio of 1:1:1, then stirring until completely dissolved, and filtering through a filter membrane to obtain a mixed metal salt solution.
[0017] According to the technical solution, the composite conductive additive is a mixture of acetylene black and multi-walled carbon nanotubes, wherein the mass ratio of acetylene black to multi-walled carbon nanotubes is 3:1.
[0018] Using the above technical solution, in step S2, the preparation process of the composite adhesive is: polyvinylidene fluoride and sodium carboxymethyl cellulose are dissolved in an aqueous solution at a mass ratio of 7:3, and stirred and dissolved at a temperature of 50-60°C to obtain a composite adhesive with a mass concentration of 3-5wt%.
[0019] Using the above technical scheme, the preparation process of the polypyrrole precursor solution is: adding pyrrole monomer to deionized water, stirring and dissolving to obtain a pyrrole monomer solution, then adding 1 mol / L ammonium persulfate solution, keeping stirring at room temperature for 30-40 minutes to obtain a polypyrrole precursor solution, wherein the pyrrole monomer accounts for 1-2wt% of the total mass of the polypyrrole precursor solution, and the weight ratio of the pyrrole monomer solution to the ammonium persulfate solution is 1:1.5.
[0020] Using the above technical solution, in step S3, the electrolyte is a solution formed by mixing potassium hydroxide, ethylene glycol and nano zirconium dioxide; the mass percentage of potassium hydroxide in the electrolyte is 35-45wt%, the mass percentage of ethylene glycol in the electrolyte is 2-3wt%, and the mass percentage of nano zirconium dioxide in the electrolyte is 0.2-0.5wt%.
[0021] Using the above technical solution, in step S3, before inserting the diaphragm, the diaphragm is immersed in a Tris buffer solution containing 2-3wt% dopamine, the pH of the solution is adjusted to 8.5, and the immersion time is 10-12h to form a uniform polydopamine coating on the diaphragm, and then the diaphragm coated with the dopamine coating is immersed in a potassium hydroxide solution with a concentration of 30-40wt% for 4-6h for pre-wetting, and the pretreated diaphragm is obtained after drying.
[0022] The technical solution also provides an alkaline battery with improved low-temperature discharge performance. The alkaline battery with improved low-temperature discharge performance is prepared by any of the above-mentioned preparation methods for an alkaline battery with improved low-temperature discharge performance.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] The positive electrode ring of the present invention adopts metal-doped composite manganese dioxide, through Ni 2 +, Co2+, Fe3+ metal ion doping and polypyrrole coating not only improve the conductivity of the material and the electrochemical activity at low temperature, but also enhance the structural stability and cycle life of the positive electrode. At the same time, the introduction of composite conductive additives can further reduce the internal resistance; the negative zinc paste can significantly reduce the hydrogen evolution side reaction and improve the utilization rate of zinc through alloying treatment of nano zinc powder and combining indium and gallium metals. At the same time, the freezing point is lowered by anti-low temperature additives to improve the reaction efficiency and fluidity of the negative zinc paste at low temperature; ethylene glycol is added to the electrolyte to lower the freezing point, and combined with nano zirconium dioxide, it can effectively improve the stability and ion migration ability of the electrolyte, thereby solving the problem of insufficient ion conductivity under low temperature conditions; the diaphragm can enhance the wettability and ion migration efficiency of the electrolyte through pre-impregnation treatment of dopamine coating and potassium hydroxide solution, avoiding the problem of increased resistance of the electrolyte in low temperature environment; the overall process effectively improves the ion conduction, electron transmission and interface stability in low temperature environment through the coordinated optimization of various materials, thereby improving the discharge capacity, output power and service life of the battery, so that it also has excellent discharge performance in extreme low temperature environment. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the description of the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" described below means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms is not necessarily for the same embodiment or example. Moreover, the technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.
[0026] The present invention provides a method for preparing an alkaline battery with improved low-temperature discharge performance, comprising the following steps:
[0027] S1. Preparation of positive electrode ring of battery: The positive electrode material of the battery contains the following components in parts by weight: 90-110 parts of metal-doped composite manganese dioxide, 1-2 parts of adhesive, and 8-12 parts of potassium hydroxide solution with a concentration of 30-40wt%. The positive electrode material and water are stirred and mixed in a mass ratio of 10-15:1 to form a positive electrode powder, and then the positive electrode ring is obtained by pressing and screening. By doping with metal ions, the conductivity and electrochemical reaction activity of manganese dioxide can be improved. The adhesive can improve the bonding strength between the positive electrode material particles to prevent the material from falling off or pulverizing in subsequent processing, thereby maintaining the stability of the electrode structure. The potassium hydroxide solution with a concentration of 30-40wt% can improve the ionic conductivity of the electrode on the one hand, and provide the necessary electrolyte environment for the positive electrode reaction on the other hand. The positive electrode material and water are mixed in a mass ratio of 10-15:1 to form a powder, which can not only ensure the uniform dispersion of the positive electrode material, but also provide appropriate viscosity and plasticity for the pressing and molding of the positive electrode ring, thereby ensuring the accuracy and stability of the positive electrode ring molding.
[0028] S2. Preparation of negative electrode zinc paste for battery: nano zinc powder, indium powder and gallium powder are mixed in a mass ratio of 92:4:4, and the mixed powder is mechanically ball-milled under argon protection to obtain alloyed zinc powder, and then the alloyed zinc powder is ultrasonically mixed with a composite conductive additive with a mass percentage of 2-4wt%, and then a composite binder with a mass percentage of 10-15wt% is added to the mixture, and the mixture is stirred evenly to form a slurry, and an anti-low temperature additive with a mass percentage of 5-7wt% is added to the slurry, and the negative electrode zinc paste is obtained after being treated by a high-speed shear disperser for 30-60 minutes; nano zinc powder, indium powder and gallium powder are mixed in a ratio of 92:4:4 and then mechanically ball-milled to form a uniform zinc-based alloy with indium and gallium. This alloying treatment can reduce Low zinc hydrogen evolution side reaction, because indium and gallium can form a stable alloy phase on the surface of zinc particles, hindering the direct contact between zinc and electrolyte, thereby improving the utilization rate of zinc powder and extending battery life; in addition, argon protection is used during the ball milling process to prevent zinc and other metal powders from oxidizing during high-energy ball milling and maintain their activity; acetylene carbon black has high conductivity and specific surface area, while multi-walled carbon nanotubes have excellent electron transmission ability and structural strength. The combination of the two forms a composite conductive additive, which can establish a continuous electron transmission path in the zinc paste, thereby improving the conductivity of the zinc paste and ensuring that the battery still has good discharge capacity in a low temperature environment; the composite binder can enhance the bonding force between zinc paste particles and between the zinc paste and the electrode current collector to prevent the negative zinc paste from falling off;
[0029] Among them, the anti-low temperature additive is a deep eutectic solution, propylene glycol and 1-ethyl-3-methylimidazolium tetrafluoroborate in a mass ratio of 6-8:2-3:0.5-1, and the deep eutectic solution is a transparent liquid formed by stirring and mixing choline chloride and ethylene glycol in a molar ratio of 1:2; the deep eutectic solution is formed by mixing choline chloride and ethylene glycol in a molar ratio of 1:2, has a low freezing point and good ionic conductivity, can remain liquid at low temperatures, and reduce the ion migration resistance of the electrolyte caused by freezing; propylene glycol acts as an antifreeze agent, which further improves the fluidity and reaction efficiency of the zinc paste in a low temperature environment by increasing the viscosity of the system and lowering the freezing point; 1-ethyl-3-methylimidazolium tetrafluoroborate acts as a low-temperature ionic liquid, has good ionic conductivity and electrochemical stability, can maintain ion conductivity at low temperatures, and promote the electrochemical reaction of the zinc negative electrode.
[0030] S3. Insert the positive electrode ring obtained in step S1 into the battery steel shell, insert a diaphragm into the positive electrode ring, and then inject electrolyte into the diaphragm. After eliminating bubbles by vacuuming, let it stand for 30-40 minutes until the electrolyte completely infiltrates the diaphragm. The diaphragm separates the positive electrode and the negative electrode to prevent direct contact between the two and cause a short circuit. At the same time, the diaphragm has a porous structure, which allows the electrolyte to infiltrate and retain inside it and provide a channel for ion conduction. The vacuuming process eliminates bubbles to avoid the generation of bubbles during the electrolyte injection process, and avoids the existence of bubbles that hinder the full contact between the electrolyte and the positive electrode and the diaphragm to form a blind spot for ion transmission.
[0031] S4, injecting the negative electrode zinc paste obtained in step S2 into the battery steel shell, inserting the negative electrode current collector, and obtaining an alkaline battery with improved low-temperature discharge performance after sealing and packaging.
[0032] Furthermore, the preparation process of the metal-doped composite manganese dioxide is as follows: manganese dioxide powder, carbon nanotubes and graphene are mixed in a mass ratio of 96:2:2, ethanol with a mass ratio of 20-40wt% is added to promote dispersion, and then placed in an ultrasonic disperser for treatment for 30-60min, and then a polypyrrole precursor solution with a mass ratio of 1-2wt% is added, and an in-situ polymerization reaction is carried out at 50-60°C for 1-2h to obtain a composite manganese dioxide coated with a conductive polymer, and then it is subjected to metal ion doping treatment to obtain a metal-doped composite manganese dioxide. Carbon nanotubes have excellent electronic conductivity, while graphene has high conductivity and large specific surface area. The synergistic effect of the two can form a continuous electron transmission channel between manganese dioxide particles, thereby improving the overall conductivity. By adding 20-40% ethanol and placing it in an ultrasonic disperser for 30-60 minutes, the conductive additive and manganese dioxide particles can be effectively dispersed evenly, and the agglomeration phenomenon can be eliminated to make the material mixing more uniform, ensuring that in the subsequent polymerization reaction, the conductive polymer can be evenly coated on the surface of the manganese dioxide particles; polypyrrole, as an intrinsic conductive polymer, still has excellent electronic conductivity in a low temperature environment. Electrical properties: by in-situ polymerization, it can be evenly coated on the surface of manganese dioxide particles, which can improve the electron transmission efficiency of the material and protect the particles from erosion by the electrolyte. Polypyrrole can also improve the cycle stability of manganese dioxide and avoid performance degradation caused by repeated expansion or dissolution of particles during operation. On the basis of coating with conductive polymer, the composite manganese dioxide is doped with metal ions, which can partially replace the manganese ions in the manganese dioxide lattice, thereby changing the electronic structure of the material, reducing the activation energy of its electrochemical reaction, and increasing the specific capacity of the material and the reaction activity at low temperature, thereby enhancing the structural stability and cycle life of the material.
[0033] Furthermore, the specific process of metal ion doping treatment is: placing the composite manganese dioxide coated with the conductive polymer in a mixed metal salt solution with a concentration of 0.1-0.2 mol / L at a mass volume ratio of 1:50, and performing a solvent thermal reaction at 105-120°C for 4-6 hours to form a composite manganese dioxide preliminarily doped with metal ions; wherein the mixed metal salt solution contains Ni 2 +, Co2+ and Fe3+ metal ions, and the molar ratio of the metal examples is 1:1:1, then the composite manganese dioxide preliminarily doped with metal ions is filtered and washed, and placed in a 0.5 mol / L nickel nitrate hexahydrate solution at a mass volume ratio of 1:30, soaked for 6-12 hours under stirring conditions to enhance the doping depth, and then dried at 65-80°C, and calcined at 525-550°C for 2-3 hours under argon protection to obtain metal-doped composite manganese dioxide. By reacting in a solvent thermal environment of 105-120°C for 4-6 hours, the metal ions diffuse into the lattice of manganese dioxide, accelerate the chemical reaction between the metal ions and the surface of manganese dioxide, and at the same time, these metal ions replace part of the manganese ions to form a stable metal-doped composite manganese dioxide; Ni 2 + can reduce the crystal defects of the material and improve the conductivity; Co2+ has strong electronic synergy and effectively reduces the electrochemical reaction impedance of manganese dioxide; Fe3+ can improve the specific capacity and low-temperature activity of the material by changing the lattice constant and redox characteristics of manganese dioxide. Through this multi-metal doping strategy, the conductivity and chemical stability of the material can be improved, so that it has excellent performance under low temperature conditions. Subsequently, the unreacted metal salts and by-products are removed by filtering and washing, and the material is placed in a 0.5 mol / L hexahydrate nickel nitrate solution at a mass volume ratio of 1:30. In this way, the doping depth of nickel ions can be enhanced, so that nickel ions can fully penetrate into the lattice of manganese dioxide to form a stable nickel-doped area, thereby improving the long-term stability and conductivity of the material.
[0034] Furthermore, the preparation process of the mixed metal salt solution is: dissolving nickel nitrate hexahydrate, cobalt nitrate hexahydrate and iron nitrate nonahydrate in deionized water at a molar ratio of 1:1:1, then stirring until completely dissolved, and filtering through a filter membrane to obtain a mixed metal salt solution.
[0035] Furthermore, the composite conductive additive is a mixture of acetylene carbon black and multi-walled carbon nanotubes, wherein the mass ratio of acetylene carbon black to multi-walled carbon nanotubes is 3:1. Acetylene carbon black is a carbon material with high specific surface area and excellent electrical conductivity. Its three-dimensional disordered structure can provide a large number of electron conduction channels, thereby effectively reducing the resistance of the electrode material. At the same time, due to its small particle size and high surface activity, it can be evenly distributed in the electrode material, fill tiny pores, and further improve the conductivity of the material; and multi-walled carbon nanotubes have a unique hollow tubular structure and high electron mobility, which can form a one-dimensional conductive network and provide an efficient transmission path for electrons in the electrode.
[0036] Furthermore, in step S2, the preparation process of the composite adhesive is: polyvinylidene fluoride and sodium carboxymethyl cellulose are dissolved in an aqueous solution at a mass ratio of 7:3, and stirred and dissolved at a temperature of 50-60°C to obtain a composite adhesive with a mass concentration of 3-5wt%. By mixing polyvinylidene fluoride and carboxymethyl cellulose in a mass ratio of 7:3, the synergistic effect of the two materials can be fully exerted. Polyvinylidene fluoride can provide excellent bonding performance and mechanical strength, while carboxymethyl cellulose can improve the fluidity of the composite adhesive and the wettability of the electrochemical interface, ensuring that the zinc paste has both excellent bonding ability and can fully contact with the electrolyte during molding and use, thereby improving the reaction efficiency; adopting stirring and dissolving at a temperature of 50-60°C can accelerate the swelling and dissolution of polyvinylidene fluoride, while maintaining the stability of carboxymethyl cellulose and preventing its molecular structure from being degraded due to excessive temperature; preparing the two into an aqueous solution with a mass concentration of 3-5wt%, can provide appropriate fluidity and viscosity for the preparation of the zinc paste, ensure that the zinc paste is evenly distributed during stirring and injection, and avoid excessive viscosity caused by excessive concentration, thereby affecting the processability of the zinc paste.
[0037] Further, the preparation process of the polypyrrole precursor solution is as follows: pyrrole monomer is added to deionized water, and after stirring and dissolving, a pyrrole monomer solution is obtained, and then 1 mol / L ammonium persulfate solution is added, and the polypyrrole precursor solution is obtained after stirring at room temperature for 30-40 minutes, wherein the pyrrole monomer accounts for 1-2wt% of the total mass of the polypyrrole precursor solution, and the weight ratio of the pyrrole monomer solution to the ammonium persulfate solution is 1:1.5. The ammonium sulfate solution, as an oxidant, can induce an oxidative polymerization reaction of the pyrrole monomer.
[0038] Further, in step S3, the electrolyte is a solution formed by mixing potassium hydroxide, ethylene glycol and nano zirconium dioxide, wherein the mass percentage of potassium hydroxide in the electrolyte is 35-45wt%, the mass percentage of ethylene glycol in the electrolyte is 2-3wt%, and the mass percentage of nano zirconium dioxide in the electrolyte is 0.2-0.5wt%. Ethylene glycol can lower the freezing point of the electrolyte, and at the same time, through its viscosity characteristics, it can improve the fluidity and wettability of the electrolyte in a low temperature environment, avoid the ion migration obstruction caused by low temperature freezing, thereby ensuring the continuous discharge capacity of the battery under low temperature conditions; nano zirconium dioxide can further improve the stability and conductivity of the electrolyte, and nano zirconium dioxide has a large specific surface area and excellent chemical stability, and can be dispersed in the electrolyte to form a microscopic stable system, thereby reducing the bubble generation and oxygen evolution phenomenon in the electrolyte. At the same time, its unique surface characteristics can improve the interface performance between the electrolyte and the electrode surface, reduce the ion migration resistance, and improve the ion transmission efficiency in a low temperature environment.
[0039] Furthermore, in step S3, before inserting the diaphragm, the diaphragm is immersed in a Tris buffer solution containing 2-3wt% dopamine, the pH of the solution is adjusted to 8.5, and the immersion time is 10-12h to form a uniform polydopamine coating on the diaphragm, and then the diaphragm coated with the dopamine coating is immersed in a potassium hydroxide solution with a concentration of 30-40wt% for 4-6h for pre-wetting, and the pretreated diaphragm is obtained after drying. Soaking the diaphragm in a Tris buffer solution containing 2-3wt% dopamine and adjusting the pH of the solution to 8.5 can induce a self-polymerization reaction of dopamine, thereby forming a uniform polydopamine coating on the surface of the diaphragm; polydopamine is a bionic coating material with stable chemical properties and good hydrophilicity, which can significantly reduce the surface energy of the diaphragm and enhance the wetting ability of the diaphragm to the electrolyte, thereby improving the ion transmission channel of the diaphragm under low temperature conditions; in addition, the polydopamine coating has certain chemical functionality, which can improve the diaphragm to Tolerance to alkaline electrolyte, avoiding structural degradation or performance decline due to long-term contact with potassium hydroxide solution; then, the diaphragm coated with polydopamine is immersed in a 30-40wt% potassium hydroxide solution for 4-6 hours of pre-wetting treatment, in order to allow the electrolyte to fully penetrate into the microporous structure of the diaphragm, thereby improving the lyophilicity and ion migration ability of the diaphragm. Through pre-wetting, the diaphragm can reach a stable electrochemical working state faster in actual use, avoiding performance fluctuations caused by uneven distribution of the electrolyte in the initial stage.
[0040] Example 1
[0041] Embodiment 1 of the present invention provides a method for preparing an alkaline battery with improved low-temperature discharge performance, comprising the following steps:
[0042] S1. Preparation of a positive electrode ring of a battery: The positive electrode material of the battery contains the following components in parts by weight: 90 parts of metal-doped composite manganese dioxide, 1 part of a binder, and 8 parts of a 30wt% potassium hydroxide solution. The positive electrode material and water are stirred and mixed in a mass ratio of 10:1 to form a positive electrode powder, and then the positive electrode ring is obtained by pressing, molding, and screening;
[0043] The preparation process of the metal-doped composite manganese dioxide is as follows: manganese dioxide powder, carbon nanotubes and graphene are mixed in a mass ratio of 96:2:2, and ethanol accounting for 20wt% by mass is added to promote dispersion;
[0044] Subsequently, the mixture was placed in an ultrasonic disperser for treatment for 30 minutes, and then a polypyrrole precursor solution with a mass proportion of 1wt% was added, and an in-situ polymerization reaction was carried out at 50°C for 1 hour to obtain a composite manganese dioxide coated with a conductive polymer, and then it was subjected to metal ion doping treatment to obtain a metal-doped composite manganese dioxide; wherein, the preparation process of the polypyrrole precursor solution is: pyrrole monomer is added to deionized water, and after stirring and dissolving, a pyrrole monomer solution is obtained, and then 1mol / L ammonium persulfate solution is added, and the polypyrrole precursor solution is obtained after stirring at room temperature for 30 minutes, wherein the pyrrole monomer accounts for 1wt% of the total mass of the polypyrrole precursor solution, and the weight ratio of the pyrrole monomer solution to the ammonium persulfate solution is 1:1.5.
[0045] The specific process of metal ion doping treatment is: placing the composite manganese dioxide coated with a conductive polymer in a mixed metal salt solution with a concentration of 0.1 mol / L at a mass volume ratio of 1:50, and performing a solvent thermal reaction at 105°C for 4 hours to form a composite manganese dioxide preliminarily doped with metal ions; wherein the mixed metal salt solution contains Ni 2 +, Co2+ and Fe3+ metal ions, and the molar ratio of the metal examples is 1:1:1, then, the composite manganese dioxide preliminarily doped with metal ions is filtered and washed, and placed in a 0.5 mol / L nickel nitrate hexahydrate solution at a mass volume ratio of 1:30, immersed for 6 hours under stirring conditions to enhance the doping depth, and then dried at 65°C, and calcined at 525°C for 2 hours under argon protection to obtain the metal-doped composite manganese dioxide;
[0046] The preparation process of the mixed metal salt solution is as follows: dissolving nickel nitrate hexahydrate, cobalt nitrate hexahydrate and iron nitrate nonahydrate in deionized water at a molar ratio of 1:1:1, then stirring until completely dissolved, and filtering through a filter membrane to obtain a mixed metal salt solution.
[0047] S2. Prepare a negative electrode zinc paste for a battery: mix nano zinc powder, indium powder and gallium powder in a mass ratio of 92:4:4, mechanically ball-mill the mixed powder under argon protection to obtain alloyed zinc powder, then ultrasonically mix the alloyed zinc powder with a composite conductive additive accounting for 2wt%, then add a composite binder accounting for 10wt% by mass to the mixture, stir evenly to form a slurry, add an anti-low temperature additive accounting for 5wt% by mass to the slurry, and treat it in a high-speed shear disperser for 30 minutes to obtain a negative electrode zinc paste;
[0048] Wherein, the composite conductive additive is a mixture of acetylene carbon black and multi-walled carbon nanotubes, wherein the mass ratio of acetylene carbon black to multi-walled carbon nanotubes is 3:1;
[0049] The anti-low temperature additive is a deep eutectic solution, propylene glycol and 1-ethyl-3-methylimidazolium tetrafluoroborate in a mass ratio of 8:3:1, wherein the deep eutectic solution is a transparent liquid formed by stirring and mixing choline chloride and ethylene glycol in a molar ratio of 1:2;
[0050] The preparation process of the composite adhesive is as follows: polyvinylidene fluoride and sodium carboxymethyl cellulose are dissolved in an aqueous solution at a mass ratio of 7:3, and the composite adhesive is obtained after stirring and dissolving at a temperature of 60° C. with a mass concentration of 3wt%;
[0051] S3, inserting the positive electrode ring obtained in step S1 into the battery steel shell, inserting a diaphragm into the positive electrode ring, and then injecting an electrolyte into the diaphragm, eliminating bubbles by vacuuming, and standing for 30 minutes until the electrolyte completely infiltrates the diaphragm; wherein the electrolyte is a solution formed by a mixture of potassium hydroxide, ethylene glycol and nano zirconium dioxide; the mass percentage of potassium hydroxide in the electrolyte is 35wt%, the mass percentage of ethylene glycol in the electrolyte is 2wt%, and the mass percentage of nano zirconium dioxide in the electrolyte is 0.2wt%. In addition, before inserting the diaphragm, the diaphragm is immersed in a Tris buffer solution containing 2wt% dopamine, the pH of the solution is adjusted to 8.5, and the immersion time is 10h to form a uniform polydopamine coating on the diaphragm, and then the diaphragm coated with the dopamine coating is immersed in a potassium hydroxide solution with a concentration of 30wt% for 4h for pre-infiltration, and the pretreated diaphragm is obtained after drying.
[0052] S4, injecting the negative electrode zinc paste obtained in step S2 into the battery steel shell, inserting the negative electrode current collector, and obtaining an alkaline battery with improved low-temperature discharge performance after sealing and packaging.
[0053] Example 2
[0054] Embodiment 2 of the present invention provides a method for preparing an alkaline battery with improved low-temperature discharge performance, comprising the following steps:
[0055] S1. Preparation of a positive electrode ring of a battery: The positive electrode material of the battery contains the following components in parts by weight: 110 parts of metal-doped composite manganese dioxide, 2 parts of a binder, and 12 parts of a 40wt% potassium hydroxide solution. The positive electrode material and water are stirred and mixed in a mass ratio of 115:1 to form a positive electrode powder, and then the positive electrode ring is obtained by pressing, molding, and screening;
[0056] The preparation process of the metal-doped composite manganese dioxide is as follows: manganese dioxide powder, carbon nanotubes and graphene are mixed in a mass ratio of 96:2:2, and 40wt% of ethanol is added to promote dispersion;
[0057] Subsequently, the mixture was placed in an ultrasonic disperser for treatment for 60 minutes, and a polypyrrole precursor solution with a mass proportion of 2wt% was added, and an in-situ polymerization reaction was carried out at 60°C for 2 hours to obtain a composite manganese dioxide coated with a conductive polymer, and then it was subjected to metal ion doping treatment to obtain a metal-doped composite manganese dioxide; wherein, the preparation process of the polypyrrole precursor solution is: pyrrole monomer is added to deionized water, and a pyrrole monomer solution is obtained after stirring and dissolving, and then a 1mol / L ammonium persulfate solution is added, and the polypyrrole precursor solution is obtained after stirring at room temperature for 40 minutes, wherein the pyrrole monomer accounts for 2wt% of the total mass of the polypyrrole precursor solution, and the weight ratio of the pyrrole monomer solution to the ammonium persulfate solution is 1:1.5.
[0058] The specific process of metal ion doping treatment is: placing the composite manganese dioxide coated with a conductive polymer in a mixed metal salt solution with a concentration of 0.2 mol / L at a mass volume ratio of 1:50, and performing a solvent thermal reaction at 120°C for 6 hours to form a composite manganese dioxide preliminarily doped with metal ions; wherein the mixed metal salt solution contains Ni 2 +, Co2+ and Fe3+ metal ions, and the molar ratio of the metal examples is 1:1:1, then, the composite manganese dioxide preliminarily doped with metal ions is filtered and washed, and placed in a 0.5 mol / L nickel nitrate hexahydrate solution at a mass volume ratio of 1:30, immersed for 12 hours under stirring conditions to enhance the doping depth, and then dried at 80°C, and calcined at 550°C for 3 hours under argon protection to obtain the metal-doped composite manganese dioxide;
[0059] The preparation process of the mixed metal salt solution is as follows: dissolving nickel nitrate hexahydrate, cobalt nitrate hexahydrate and iron nitrate nonahydrate in deionized water at a molar ratio of 1:1:1, then stirring until completely dissolved, and filtering through a filter membrane to obtain a mixed metal salt solution.
[0060] S2. Prepare a negative electrode zinc paste for a battery: mix nano zinc powder, indium powder and gallium powder in a mass ratio of 92:4:4, mechanically ball-mill the mixed powder under argon protection to obtain alloyed zinc powder, then ultrasonically mix the alloyed zinc powder with a composite conductive additive accounting for 4wt% by mass, then add a composite binder accounting for 15wt% by mass to the mixture, stir evenly to form a slurry, add an anti-low temperature additive accounting for 7wt% by mass to the slurry, and treat it in a high-speed shear disperser for 60 minutes to obtain a negative electrode zinc paste;
[0061] Wherein, the composite conductive additive is a mixture of acetylene carbon black and multi-walled carbon nanotubes, wherein the mass ratio of acetylene carbon black to multi-walled carbon nanotubes is 3:1;
[0062] The anti-low temperature additive is a deep eutectic solution, glycerol and 1-ethyl-3-methylimidazolium tetrafluoroborate in a mass ratio of 6:2:0.5, wherein the deep eutectic solution is a transparent liquid formed by stirring and mixing choline chloride and ethylene glycol in a molar ratio of 1:2;
[0063] The preparation process of the composite adhesive is as follows: polyvinylidene fluoride and sodium carboxymethyl cellulose are dissolved in an aqueous solution at a mass ratio of 7:3, and the composite adhesive is obtained after stirring and dissolving at a temperature of 60° C. with a mass concentration of 5wt%;
[0064] S3, inserting the positive electrode ring obtained in step S1 into the battery steel shell, inserting a diaphragm into the positive electrode ring, and then injecting an electrolyte into the diaphragm, eliminating bubbles by vacuuming, and standing for 40 minutes until the electrolyte completely infiltrates the diaphragm; wherein the electrolyte is a solution formed by a mixture of potassium hydroxide, ethylene glycol and nano zirconium dioxide; the mass percentage of potassium hydroxide in the electrolyte is 35wt%, the mass percentage of ethylene glycol in the electrolyte is 3wt%, and the mass percentage of nano zirconium dioxide in the electrolyte is 0.5wt%. In addition, before inserting the diaphragm, the diaphragm is immersed in a Tris buffer solution containing 3wt% dopamine, adjusting the solution pH to 8.5, and the immersion time is 10h to form a uniform polydopamine coating on the diaphragm, and then immersing the diaphragm coated with dopamine in a potassium hydroxide solution with a concentration of 40wt% for 4h for pre-infiltration, and the pretreated diaphragm is obtained after drying.
[0065] S4, injecting the negative electrode zinc paste obtained in step S2 into the battery steel shell, inserting the negative electrode current collector, and obtaining an alkaline battery with improved low-temperature discharge performance after sealing and packaging.
[0066] Comparative Example 1
[0067] The alkaline battery with improved low-temperature discharge performance and its preparation method of this comparative example 1 are different from those of Example 1 in that in step S1, the positive electrode material of the battery contains the following components in parts by mass: 90 parts of manganese dioxide, 1 part of a binder, and 8 parts of a 30wt% potassium hydroxide solution.
[0068] Comparative Example 2
[0069] The alkaline battery with improved low-temperature discharge performance and the preparation method thereof of Comparative Example 2 are different from those of Example 1 in that in step S2, no composite conductive additive is added during the preparation of the negative electrode zinc paste.
[0070] Comparative Example 3
[0071] The alkaline battery with improved low-temperature discharge performance and the preparation method thereof of Comparative Example 3 are different from those of Example 1 in that in step S2, no anti-low-temperature additive is added during the preparation of the negative zinc paste.
[0072] Comparative Example 4
[0073] The alkaline battery with improved low-temperature discharge performance and the preparation method thereof of Comparative Example 4 are different from those of Example 1 in that in step S1, during the preparation of the metal-doped composite manganese dioxide, the manganese dioxide powder is not subjected to in-situ polymerization treatment with a polypyrrole precursor solution.
[0074] Comparative Example 5
[0075] The alkaline battery with improved low-temperature discharge performance and the preparation method thereof of Comparative Example 5 are different from those of Example 1 in that in step S3, the electrolyte is a potassium hydroxide solution with a concentration of 35 wt%.
[0076] Comparative Example 6
[0077] The alkaline battery with improved low-temperature discharge performance and the preparation method thereof of Comparative Example 6 are different from those of Example 1 in that in step S3, the separator is not pretreated before being inserted.
[0078] The following experiments are conducted on the above-mentioned embodiments 1-2 and comparative examples 1-6 to verify or understand their performances. In the alkaline batteries prepared in the above-mentioned embodiments 1-2 and comparative examples 1-6.
[0079]
[0080] Table 1 Comparison of alkaline battery test data at 3.9Ω continuous discharge at low temperature of -20℃
[0081]
[0082] Table 2 Comparison of alkaline battery test data at -20℃ for 43Ω continuous discharge
[0083]
[0084] Table 3 Comparison of discharge test data of alkaline batteries at low temperature of -20℃
[0085] According to Tables 1 to 3 above, it can be seen that in the alkaline batteries prepared in Examples 1 and 2, the positive electrode ring is made of metal-doped composite manganese dioxide, and the Ni 2 +, Co2+, Fe3+ metal ion doping and polypyrrole coating not only improve the conductivity of the material and the electrochemical activity at low temperature, but also enhance the structural stability and cycle life of the positive electrode. At the same time, the introduction of composite conductive additives can further reduce the internal resistance; the negative zinc paste can significantly reduce the hydrogen evolution side reaction and improve the utilization rate of zinc through alloying treatment of nano zinc powder and combining indium and gallium metals. At the same time, the freezing point is lowered by anti-low temperature additives to improve the reaction efficiency and fluidity of the negative zinc paste at low temperature; ethylene glycol is added to the electrolyte to lower the freezing point, and combined with nano zirconium dioxide, it can effectively improve the stability and ion migration ability of the electrolyte, thereby solving the problem of insufficient ion conductivity under low temperature conditions; the diaphragm can enhance the wettability and ion migration efficiency of the electrolyte through pre-impregnation treatment of dopamine coating and potassium hydroxide solution, avoiding the problem of increased resistance of the electrolyte in low temperature environment; the overall process effectively improves the ion conduction, electron transmission and interface stability in low temperature environment through the coordinated optimization of various materials, thereby improving the discharge capacity, output power and service life of the battery, so that it also has excellent discharge performance in extreme low temperature environment.
[0086] In Comparative Example 1, the positive electrode material of the battery contains the following components by mass: 90 parts of manganese dioxide, 1 part of binder, and 8 parts of 30wt% potassium hydroxide solution. Conventional manganese dioxide has a reduced electron migration rate under low temperature conditions, resulting in a slow electrochemical reaction rate of the positive electrode material, thereby reducing the discharge capacity and output power of the battery; while the metal-doped composite manganese dioxide is Ni-doped. 2 The doping of Co2+, Fe3+, and Co2+ can optimize the crystal structure of manganese dioxide and reduce the energy barrier of its electron transmission, thereby improving its conductivity and reaction activity at low temperatures.
[0087] In Comparative Example 2, no composite conductive additives were added during the preparation of the negative electrode zinc paste. Composite conductive additives such as acetylene carbon black and multi-walled carbon nanotubes have good specific surface area and electronic conductivity, and have low electron migration impedance under low temperature conditions, which can improve the reaction activity of the zinc paste under low temperature conditions. When no composite conductive additives were added to Comparative Example 2, the reaction efficiency of the zinc paste at low temperature would be greatly reduced, resulting in insufficient low-temperature discharge capacity and serious energy loss.
[0088] In Comparative Example 3, no anti-low temperature additive was added during the preparation of the negative zinc paste. The absence of the anti-low temperature additive will significantly increase the freezing point of the negative zinc paste in a low temperature environment. When the ambient temperature is lower than the freezing point of the electrolyte, the water in the zinc paste will freeze to form ice crystals. These ice crystals will hinder the full contact between the electrolyte and the zinc particles, resulting in the obstruction of ion migration, greatly reducing the electrochemical reaction activity of the zinc paste, which is manifested as a significant decrease in the discharge capacity of the battery; secondly, the zinc paste will become too viscous or solidified, thereby hindering the transmission path of ions and electrons in the zinc paste, resulting in an increase in internal resistance and a decrease in electrochemical reaction efficiency, which seriously affects the output power of the battery; the deep eutectic solution, glycerol and low-temperature ionic liquid in the anti-low temperature additive can not only reduce the freezing point of the zinc paste, but also improve the interface wettability and ion conductivity of the zinc paste in a low temperature environment;
[0089] In Comparative Example 4, during the preparation of the metal-doped composite manganese dioxide, the manganese dioxide powder was not subjected to in-situ polymerization treatment with a polypyrrole precursor solution. Polypyrrole is an intrinsically conductive polymer that can maintain excellent electronic conductivity under low temperature conditions. A uniform coating is formed on the surface of manganese dioxide through in-situ polymerization, which can effectively reduce the electron transfer resistance between particles. If the polypyrrole coating is missing, the electron transfer path between the manganese dioxide particles is discontinuous, and the conductivity is significantly reduced, resulting in a significant decrease in the electrochemical reaction efficiency of the positive electrode material at low temperatures. In addition, the polypyrrole coating can also improve the low-temperature activity of manganese dioxide. The in-situ polymerization process can introduce a large number of electron and ion active sites on the particle surface, thereby reducing the activation energy of the electrochemical reaction. If this treatment is not performed, the reaction activity of manganese dioxide at low temperatures will be poor, the electrochemical process will become slow, and the discharge performance will be attenuated.
[0090] In Comparative Example 5, the electrolyte in step S3 is a potassium hydroxide solution with a concentration of 35wt%. A single potassium hydroxide solution is easily frozen or crystallized under low temperature conditions, resulting in obstruction of the ion migration channel, thereby reducing the discharge capacity and output power of the battery; ethylene glycol, as an antifreeze agent, can ensure that the electrolyte maintains appropriate fluidity at low temperatures by lowering the freezing point of the electrolyte and improving the rheological properties, while nano zirconium dioxide has a high specific surface area and good chemical stability, which can improve the wettability and interface conductivity with the electrode surface in the electrolyte, thereby enhancing the ion migration ability in a low temperature environment.
[0091] In Comparative Example 6, the diaphragm was not pretreated before being inserted. The diaphragm without the polydopamine coating lacked the support of the surface modification layer in a low-temperature environment, and the ion migration ability was more susceptible to the influence of temperature drop. The polydopamine coating formed a uniform coating on the surface of the diaphragm through self-polymerization, which not only improved the hydrophilicity of the diaphragm, but also enhanced the adsorption capacity of the diaphragm to the electrolyte under low temperature conditions, thereby optimizing the ion conduction efficiency. If this coating is missing, the ion conduction ability of the diaphragm under low temperature conditions will be significantly reduced, resulting in a slower electrochemical reaction rate, thereby affecting the discharge performance of the alkaline battery.
[0092] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing an alkaline battery with improved low temperature discharge performance, characterized in that: The following steps are involved: S1. Preparation of a positive electrode ring of a battery: The positive electrode material of the battery contains the following components in parts by weight: 90-110 parts of metal-doped composite manganese dioxide, 1-2 parts of a binder, and 8-12 parts of a 30-40wt% potassium hydroxide solution. The positive electrode material and water are stirred and mixed in a mass ratio of 10-15:1 to form a positive electrode powder, and then the positive electrode ring is obtained by pressing, molding, and screening; S2. Prepare a negative electrode zinc paste for a battery: mix nano zinc powder, indium powder and gallium powder in a mass ratio of 92:4:4, mechanically ball-mill the mixed powder under argon protection to obtain alloyed zinc powder, then ultrasonically mix the alloyed zinc powder with a composite conductive additive accounting for 2-4wt% by mass, then add a composite binder accounting for 10-15wt% by mass to the mixture, stir evenly to form a slurry, add an anti-low temperature additive accounting for 5-7wt% by mass to the slurry, and treat it with a high-speed shear disperser for 30-60 minutes to obtain a negative electrode zinc paste; The anti-low temperature additive is a deep eutectic solution, propylene glycol and 1-ethyl-3-methylimidazolium tetrafluoroborate in a mass ratio of 6-8:2-3:0.5-1, and the deep eutectic solution is a transparent liquid formed by stirring and mixing choline chloride and ethylene glycol in a molar ratio of 1:2; S3, inserting the positive electrode ring obtained in step S1 into the battery steel shell, inserting a diaphragm into the positive electrode ring, and then injecting electrolyte into the diaphragm, eliminating bubbles by vacuuming, and standing for 30-40 minutes until the electrolyte completely infiltrates the diaphragm; S4, injecting the negative electrode zinc paste obtained in step S2 into the battery steel shell, inserting the negative electrode current collector, and obtaining an alkaline battery with improved low-temperature discharge performance after sealing and packaging.
2. The method for preparing an alkaline battery with improved low temperature discharge performance according to claim 1, characterized in that: The preparation process of the metal-doped composite manganese dioxide is as follows: manganese dioxide powder, carbon nanotubes and graphene are mixed in a mass ratio of 96:2:2, and ethanol accounting for 20-40wt% by mass is added to promote dispersion; It is then placed in an ultrasonic disperser for 30-60 minutes, and then a polypyrrole precursor solution with a mass percentage of 1-2wt% is added, and an in-situ polymerization reaction is carried out at 50-60°C for 1-2 hours to obtain a composite manganese dioxide coated with a conductive polymer, which is then doped with metal ions to obtain a metal-doped composite manganese dioxide.
3. The method for preparing an alkaline battery with improved low temperature discharge performance according to claim 2, characterized in that: The specific process of metal ion doping treatment is: placing the composite manganese dioxide coated with a conductive polymer in a mixed metal salt solution with a concentration of 0.1-0.2 mol / L at a mass volume ratio of 1:50, and performing a solvent thermal reaction at 105-120°C for 4-6 hours to form a composite manganese dioxide preliminarily doped with metal ions; wherein the mixed metal salt solution contains Ni 2 +, Co2+ and Fe3+ metal ions, and the molar ratio of the metal examples is 1:1:
1. Subsequently, the composite manganese dioxide preliminarily doped with metal ions is filtered and washed, and placed in a 0.5 mol / L nickel nitrate hexahydrate solution at a mass volume ratio of 1:30, and immersed for 6-12 hours under stirring conditions to enhance the doping depth, and then dried at 65-80°C, and calcined at a temperature of 525-550°C for 2-3 hours under argon protection to obtain the metal-doped composite manganese dioxide.
4. The method for preparing an alkaline battery with improved low temperature discharge performance according to claim 3, characterized in that: The preparation process of the mixed metal salt solution is: dissolving nickel nitrate hexahydrate, cobalt nitrate hexahydrate and iron nitrate nonahydrate in deionized water at a molar ratio of 1:1:1, then stirring until completely dissolved, and filtering through a filter membrane to obtain a mixed metal salt solution.
5. The method for preparing an alkaline battery with improved low temperature discharge performance according to claim 1, characterized in that: The composite conductive additive is a mixture of acetylene carbon black and multi-walled carbon nanotubes, wherein the mass ratio of acetylene carbon black to multi-walled carbon nanotubes is 3:
1.
6. The method for preparing an alkaline battery with improved low temperature discharge performance according to claim 1, characterized in that: In step S2, the preparation process of the composite adhesive is as follows: polyvinylidene fluoride and sodium carboxymethyl cellulose are dissolved in an aqueous solution at a mass ratio of 7:3, and stirred and dissolved at a temperature of 50-60°C to obtain a composite adhesive with a mass concentration of 3-5wt%.
7. The method for preparing an alkaline battery with improved low temperature discharge performance according to claim 1, characterized in that: The preparation process of the polypyrrole precursor solution is as follows: adding pyrrole monomer into deionized water, stirring and dissolving to obtain a pyrrole monomer solution, then adding 1 mol / L ammonium persulfate solution, and stirring at room temperature for 30-40 minutes to obtain a polypyrrole precursor solution, wherein the pyrrole monomer accounts for 1-2wt% of the total mass of the polypyrrole precursor solution, and the weight ratio of the pyrrole monomer solution to the ammonium persulfate solution is 1:1.
5.
8. The method for preparing an alkaline battery with improved low temperature discharge performance according to claim 1, characterized in that: In step S3, the electrolyte is a solution formed by mixing potassium hydroxide, ethylene glycol and nano zirconium dioxide; The mass percentage of potassium hydroxide in the electrolyte is 35-45wt%, the mass percentage of ethylene glycol in the electrolyte is 2-3wt%, and the mass percentage of nano zirconium dioxide in the electrolyte is 0.2-0.5wt%.
9. The method for preparing an alkaline battery with improved low temperature discharge performance according to claim 1, characterized in that: In step S3, before inserting the diaphragm, the diaphragm is immersed in a Tris buffer solution containing 2-3wt% dopamine, the pH of the solution is adjusted to 8.5, and the immersion time is 10-12h to form a uniform polydopamine coating on the diaphragm, and then the diaphragm coated with the dopamine coating is immersed in a potassium hydroxide solution with a concentration of 30-40wt% for 4-6h for pre-wetting, and the pretreated diaphragm is obtained after drying.
10. An alkaline battery with improved low temperature discharge performance, characterized in that: The alkaline battery is prepared by the preparation method for improving low-temperature discharge performance of the alkaline battery according to any one of claims 1 to 9.
Citation Information
Cited By
Low-temperature-resistant electrolyte for alkaline battery and preparation method of low-temperature-resistant electrolyte
CN120674624A
Low-temperature-resistant electrolyte for alkaline batteries and preparation method thereof
CN120674624B
Positive electrode material of secondary zinc-manganese battery, preparation method of positive electrode material and secondary zinc-manganese battery
CN120767295A
A secondary zinc-manganese battery cathode material, preparation method, and secondary zinc-manganese battery
CN120767295B
Low-temperature electrolyte preparation device and method for zinc-silver reserve battery
CN122000373A